India-Pakistan in war & peace - Dixit, J. N. (Jyotindra Nath), 1936-2005.; T&F eBooks (London : Routledge, 2002)
Survey of India-Pakistan relations from post1947 onwards to present day.
First published 2002 in India by Books Today.
Includes index.
Also available in print edition.
Electronic reproduction.
Keywords: India -- Foreign relations -- Pakistan; Pakistan -- Foreign relations -- India; India -- Foreign relations -- 1947-1984.; India -- Foreign relations -- 1984-; Electronic books